Nisa’- menstrual in Islamic perspective in informative mobile application - Ruslan, Zahrulatikah (2019)
Fiqh thaharah especially in relation to women's blood problems is often a debate. Efforts to provide understanding to women, should be done because they are closelyrelated to the perfection of worship. The purpose of the project researcharetodeliver information about menstrual and basic guide in calculation based onIslamicperspective. The objective of this project are to identify the requirement for Nisa-Menstrual in Islamic Perspective of Informative Mobile Application, to designNisa-Menstrual in Islamic Perspective of Informative Mobile Application, to developNisa- Menstrual in Islamic Perspective of Informative Mobile Application. The scopeofthis project are for the public user to gain information and learning about themenstrual. The knowledge of the menstrual are important for themto knowhowthe right calculation are implement and the knowledge from Islamic perspective. Inthis project there are four different button and function which are Haid, Istihadah, Nfas, Q&A and Cara Pengiraan. This project used Mobile Development LifeCycleas the methodology approach to the development of Nisa - Menstrual inIslamicPerspective of Informative Mobile Application. Mobile Development Life Cycleisdivided into seven stages which identification, design, development, prototyping, testing, deployment, maintenance. As the conclusion, Nisa - Menstrual inIslamicPerspective of Informative Mobile Application may give benefit to publer user togain more information in order make a right calculation in menstrual.